2016
DOI: 10.7150/ijms.15548
|View full text |Cite
|
Sign up to set email alerts
|

Differential microRNA Profiles Predict Diabetic Nephropathy Progression in Taiwan

Abstract: Objectives: Diabetic nephropathy (DN) is a major leading cause of kidney failure. Recent studies showed that serological microRNAs (miRs) could be utilized as biomarkers to identify disease pathogenesis; the DN-related miRs, however, remained to be explored. Methods: A prospective case-control study was conducted. The clinical significance of five potential miRs (miR-21, miR-29a, miR-29b, miR-29c and miR192) in type 2 Diabetes Mellitus (T2DM) patients who have existing diabetic retinopathy with differential Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 42 publications
(45 reference statements)
5
41
1
5
Order By: Relevance
“…For instance, diabetic nephropathy (DN) is one of the most serious complications of diabetes. Recently, a prospective case-control study showed that miR-21 , miR-29a/b/c , and miR-192 reflect DN pathogenesis and could be of clinical significance to monitor and prevent DN advancement [66]. miR-21 was shown to suppress PTEN , a key modulator in DN [67]; miR-192 was shown to suppress ZEB2 , which is responsible for controlling TGF-β-induced extracellular matrix proteins accumulating during DN [67], while miR-29c was shown to inhibit SPRY1 , which involves albuminuria and kidney mesangial matrix accumulation in diabetic mice models [68].…”
Section: Mirnas As Type 2 Diabetes (T2dm) Markers and Its Complicamentioning
confidence: 99%
“…For instance, diabetic nephropathy (DN) is one of the most serious complications of diabetes. Recently, a prospective case-control study showed that miR-21 , miR-29a/b/c , and miR-192 reflect DN pathogenesis and could be of clinical significance to monitor and prevent DN advancement [66]. miR-21 was shown to suppress PTEN , a key modulator in DN [67]; miR-192 was shown to suppress ZEB2 , which is responsible for controlling TGF-β-induced extracellular matrix proteins accumulating during DN [67], while miR-29c was shown to inhibit SPRY1 , which involves albuminuria and kidney mesangial matrix accumulation in diabetic mice models [68].…”
Section: Mirnas As Type 2 Diabetes (T2dm) Markers and Its Complicamentioning
confidence: 99%
“…There is in vivo evidence that microRNA (miR)-29c knockdown or miR-27a knockdown compromises progression of diabetic nephropathy. [8,9] Furthermore, Chien et al [10] have found that miR-21, miR-29a/b/c, and miR-192 are involved in pathogenesis of diabetic neuropathy and might be suggested as biomarkers of progression of diabetic neuropathy. Despite these achievements, the molecular mechanisms behind the diabetic neuropathy have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Mountainous research has demonstrated that altered levels of miRNAs were involved in the progression of many diseases, DKD included. Increasing studies have proved that in the progression of DKD, various miRNAs had positive correlation with fibrosis such as miR‐21, miR‐192, miR‐377 and miR‐491, while miR‐23b, miR‐29a, miR‐29b and miR‐200 were the opposite . Our previous bioinformatical study has found the expression of miR‐326‐3p in kidney tissue was significantly decreased in patients with DKD compared with the normal control .…”
Section: Discussionmentioning
confidence: 88%
“…Increasing studies have proved that in the progression of DKD, various miRNAs had positive correlation with fibrosis such as miR-21, miR-192, miR-377 and miR-491, while miR-23b, miR-29a, miR-29b and miR-200 were the opposite. 28,29 Our previous bioinformatical study has found the expression of miR-326-3p in kidney tissue was significantly decreased in patients with DKD compared with the normal control. 20 Recently, miR-326-3p was identified to be an important regulator of fibrosis in idiopathic pulmonary fibrosis (ITP), lung cancer and systemic lupus erythematosus (SLE).…”
Section: Discussionmentioning
confidence: 99%